AN ANALYSIS OF TEACHERS’ PEDAGOGIC COMPETENCE IN TEACHING ENGLISH AT SMP NEGERI 2 LOTU IN 2023/2024 - Gea, Putri Dewi Darmayanti; Telaumbanua, Yasminar Amaerita; Daeli, Hidayati; Laoli, Adieli (Universitas Muhammadiyah Makassar, 2024)
Teacher pedagogic competence affects the achievement of effective and quality learning, where teachers are expected to master all indicators of pedagogic competence. However, in the learning process that occurs, pedagogic competence is still not maximally applied by English teachers at SMP Negeri 2 Lotu. The purpose of this research was to find out what are the teachers’ pedagogic competences used by the teachers in teaching English and to find out the factors that influence teachers' pedagogic competence in teaching English. The method used in this research is qualitative analysis. The instruments were observation, interview and documentation. Data were obtained from observation which were then analyzed to reveal teachers' pedagogic competence. Data from interviews were analyzed to find out the factors that influence teachers' pedagogic competence in teaching English. Data from documentation used as relevant data to support in the research. After analyzing the pedagogic competence of teachers through observation and interviews, indicators of pedagogic competence that they used, namely mastering the characteristics of learners from the physical, moral, spiritual, social, cultural, emotional, and intellectual aspects, mastering learning theory and learning principles, facilitating the development of students' potential to actualize their various potential, organizing assessment and evaluating of learning processes and outcomes. Pedagogic competence that English teachers do not yet have are mastering learning theory and learning principles, utilizing information and communication technology for learning purposes and developing the curriculum related to the subjects taught. This is due to several factors, namely teaching experience, educational facilities, teacher income and principal supervision.